Chocolate, Air Pollution and Children's Neuroprotection: What Cognition Tools should be at Hand to Evaluate Interventions? - Calderón-Garcidueñas, Lilian; San Juan Chávez, Vanessa; Vacaseydel-Aceves, Nora B.; Calderón-Sánchez, Raymundo; Macías-Escobedo, Edgar; Frías, Carmen; Giacometto, Marcela; Velasquez, Luis; Félix-Villarreal, Renata; Martin, Jessie D.; Draheim, Christopher; Engle, Randall W. (Frontiers in Pharmacology, 2016)
Millions of children across the world are exposed to multiple sources of indoor and outdoor air pollutants, including high concentrations of fine particulate matter (PM2.5) and ozone (O3). The established link between exposure to PM2.5, brain structural, volumetric and metabolic changes, severe cognitive deficits (1.5-2SD from average IQ) in APOE 4 heterozygous females with >75% to <94% BMI percentiles, and the presence of Alzheimer’s disease (AD) hallmarks in urban children and young adults necessitates exploration of ways to protect these individuals from the deleterious neural effects of pollution exposure. Emerging research suggests that cocoa interventions may be a viable option for neuroprotection, with evidence suggesting that early cocoa interventions could limit the risk of cognitive and developmental concerns including: endothelial dysfunction, cerebral hypoperfusion, neuroinflammation, and metabolic detrimental brain effects. Currently, however, it is not clear how early we should implement consumption of cocoa to optimize its neuroprotective effects. Moreover, we have yet to identify suitable instruments for evaluating cognitive responses to these interventions in clinically healthy children, teens, and young adults. An approach to guide the selection of cognitive tools should take into account neuropsychological markers of cognitive declines in patients with Alzheimer’s neuropathology, the distinct patterns of memory impairment between early and late onset Alzheimer’s disease (AD), and the key literature associating white matter integrity and poor memory binding performance in cases of asymptomatic familial AD. We highlight potential systemic and neural benefits of cocoa consumption. We also highlight Working Memory Capacity (WMC) and attention control tasks as opened avenues for exploration in the air pollution scenario. Exposures to air pollutants during brain development have serious brain consequences in the short and long term and reliable cognition tools should be at hand to evaluate interventions.